Rasio Biji Hanjeli (Coix Lacryma-Jobi L.) dan Kacang Kenari (Canarium Indicum L.) pada Granola - Stevany Angelika Putri; Suko Priyono; Maherawati Maherawati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Granola bar is an instant snack product in the form of a bar that has high nutritional value and generally commercial products use imported ingredients such as oats and almonds, but can be developed using local food ingredients such as Job's Tears seeds and walnuts that have high nutritional content such as carbohydrates, protein, fiber, fat, and antioxidants. This study aims to obtain the ratio of Job's Tears seeds and walnuts to produce granola bars with the best physicochemical and organoleptic characteristics. The method used is a Randomized Block Design (RBD) with one treatment factor in the form of the ratio of Job's Tears seeds and walnuts (100:0, 80:20, 70:30, 60:40, and 50:50) with five replications to obtain 25 experimental units. Data were analyzed using Analysis of Variance (ANOVA) and Honestly Significant Difference (HSD) test. The results showed that the ratio of Job's Tears seeds and walnuts significantly affected the levels of fat, protein, carbohydrate, total calories, as well as organoleptic attributes including taste, aroma, texture, and overall preference. This research contributes to efforts Granola bar is an instant snack product in the form of a bar that has high nutritional value and generally commercial products use imported ingredients such as oats and almonds, but can be developed using local food ingredients such as Job's Tears seeds and walnuts that have high nutritional content such as carbohydrates, protein, fiber, fat, and antioxidants. This study aims to obtain the ratio of Job's Tears seeds and walnuts to produce granola bars with the best physicochemical and organoleptic characteristics. The method used is a Randomized Block Design (RBD) with one treatment factor in the form of the ratio of Job's Tears seeds and walnuts (100:0, 80:20, 70:30, 60:40, and 50:50) with five replications to obtain 25 experimental units. Data were analyzed using Analysis of Variance (ANOVA) and Honestly Significant Difference (HSD) test. The results showed that the ratio of Job's Tears seeds and walnuts significantly affected the levels of fat, protein, carbohydrate, total calories, as well as organoleptic attributes including taste, aroma, texture, and overall preference. This research contributes to efforts to diversify local Indonesian food as raw materials for highly nutritious functional food products diversify local Indonesian food as raw materials for highly nutritious functional food products.